2004
DOI: 10.1097/01.tp.0000120385.03278.28
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Amino Acid Triplet Differences Between Patient and Donor Is Predictive for the Antibody Reactivity Against Mismatched Human Leukocyte Antigens1

Abstract: These results indicate that the immunogenicity of the fetus is lower than that of a rejected kidney and that analysis of the number of triplet mismatches can predict the antibody reactivity against the mismatched HLA antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 12 publications
6
79
0
1
Order By: Relevance
“…Although HLA-DQ and -DR may be closely related at an antigen level, it has been shown that small differences in one or more epitopes between donors and recipients at either locus are sufficient to generate a humoral and/or T cell-mediated immune response (18,19). In a nested casecontrol study of a cohort of 52 kidney transplant recipients with established transplant glomerulopathy, an increasing number of HLA-DQ and HLA-DR eplet mismatches was associated with an increased risk of developing transplant glomerulopathy, suggesting that epitope mismatches at either HLA-DQ or HLA-DR locus are equally important in predicting graft outcomes (5).…”
Section: Discussionmentioning
confidence: 99%
“…Although HLA-DQ and -DR may be closely related at an antigen level, it has been shown that small differences in one or more epitopes between donors and recipients at either locus are sufficient to generate a humoral and/or T cell-mediated immune response (18,19). In a nested casecontrol study of a cohort of 52 kidney transplant recipients with established transplant glomerulopathy, an increasing number of HLA-DQ and HLA-DR eplet mismatches was associated with an increased risk of developing transplant glomerulopathy, suggesting that epitope mismatches at either HLA-DQ or HLA-DR locus are equally important in predicting graft outcomes (5).…”
Section: Discussionmentioning
confidence: 99%
“…The humoral alloimmune response to HLA class I mismatches can be successfully predicted by the HLAMatchmaker algorithm (20,21). As HLAMatchmaker takes only Ab-accessible sites of the HLA molecules into consideration, it is not a suitable tool to predict T cell alloreactivity (22).…”
mentioning
confidence: 99%
“…Lobashevsky et al 26 examined sera from highly sensitized renal transplant candidates and found that the number of highly immunogenic triplet mismatches between donor-recipient pairs reliably predicted final crossmatch results. 26 Dankers et al 22 showed a strong correlation between the numbers of triplet mismatches between donors and renal transplant recipients and the development of donor-specific antibodies in these patients, further validating the HLAMatchmaker algorithm. 22 This is the first report of platelet transfusion outcomes when HLA-A and -B locus compatibility between donors and alloimmunized recipients is defined by the HLAMatchmaker program.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that patients' antibody reactivity correlates with the number of mismatched triplets against donor HLA antigens. 22 This example illustrates that some CREG matches are structurally compatible, but others have considerable numbers of mismatched triplets. Conversely, certain antigens that are not considered cross-reacting for this patient's HLA antigens have fewer mismatched triplets.…”
Section: Hlamatchmakermentioning
confidence: 99%